Use of Lean-Sigma as a Problem-Solving Method in a Restrictive Environment - Alba-Baena, Noé (Springer, Cham, 2018)
This chapter presents the use of Lean-Sigma methodology and tools in a Latin American restrictive environment where time, economic, and technological limitations are common. These conditions limits the use of solutions such as reengineering and major technological investments. The mentioned restrictive characteristics are the perfect scenario for the use of fast and efficient solutions for customer-focused challenges. Lean-Sigma is a fast responder methodology focused on problem-solving using the effective approach of Lean Manufacturing combined with the statistical analysis of Six-Sigma. The use of Lean-Sigma methodology has been previously reported, and its value proved as an efficient solving methodology in highly restrictive environments. However, this chapter describes the inclusion of Design for Six Sigma (DFSS). After the initial considerations, an example related to a production problem in an exterior-home products, is described from a manufacturing facility at Juarez, Mexico. The project is focused on a brass component for outdoor lighting products. The customer complaints shows that this component comes from the supplier with differences in color and tones, through the combination of Lean-Sigma and DFSS a solution is given. The solution includes the design of a qualitative measuring device, the modification of a cleaning process, and the standardization of the chemical coloring process (Patina). Once validated, the designed device was also used for determining the acceptance levels at the incoming inspection station and was incorporated into the quality control station. Finally, the results and knowledge were successfully transferred to the supplier. The results shows that the combination of Lean-Sigma with the DFSS methodologies and their tools can satisfactorily be used in a restrictive environment.